Sjogren's Syndrome - Pyar Ali Fazel; Karim ullah Makki; Hussain Haroon; Saira Sheikh (Journal of the Dow University of Health Sciences, 2007)
Sjogen's syndrome is an autoimmune and a chronic inflammatory disorder characterized by the infilrration of the exocrine glands particulary the lacrimal and the salivary glands by the lymphocytes and the plasma cells resulting in xerostomia and xerophthalamia.